Study trends on Resilience of Nursing Students -Focusing on nursing journals published in South Korea-: Study trends on Resilience of Nursing Students - Kang, Se-Won (Advances in Social Sciences Research Journal, 2022)
This study is a literature review to understand the trends in the nursing students’ resilience published in nursing journals in South Korea. Among the papers published in nursing journals in South Korea, the research papers included “resilience” and “nursing students.” As a result of the search, 40 papers suitable for literature review, which included three experimental studies and 37 descriptive studies, were selected for relational and factor analysis. The most frequently used variables along with resilience were self-esteem, self-leadership, depression, and emotional intelligence. In the future, intervention studies to strengthen the resilience of nursing students should be conducted.